Primary breast lymphoma initially diagnosed as invasive ductal carcinoma: A case report. Issue 6 (5th May 2021) - Uenaka, Natsuki; Yamamoto, Shinya; Sato, Seiya; Kudo, Takamichi; Adachi, Shoko; Narui, Kazutaka; Tanabe, Mikiko; Yamada, Akimitsu; Ishikawa, Takashi; Endo, Itaru
Abstract: A malignant tumor in the breast may not be conclusive of breast cancer. It is important to keep the possibility of primary breast lymphoma in rare scenarios. For the diagnosis of primary breast lymphoma, immunohistochemical staining is necessary. Abstract : A malignant tumor in the breast may not be conclusive of breast cancer. It is important to keep the possibility of primary breast lymphoma in rare scenarios. For the diagnosis of primary breast lymphoma, immunohistochemical staining is necessary.